Analisis Strategi Retorika Dakwah Fuadh Naim terhadap Penggemar Hallyu pada Saluran YouTube “Fuadh Naim Official” - Safitri, Nur; Efendi, Erwan (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The purpose of this research is to investigate the preaching rhetorical style that Fuadh The most popular social networking app in Indonesia is YouTube. According to Google, 127 million YouTube viewers will log in every month by 2022. Indonesia has 205 million internet users. YouTube's huge user base makes it ideal for preaching. The use of the internet can improve fraternal relationships and provide quick information. The purpose of this study is to investigate the rhetorical style of preaching that Fuadh Naim uses on the YouTube channel known as “Fuadh Naim Official” to target Hallyu supporters. For information gathering purposes, non-participant observation of Fuadh Naim's da'wah films was used along with Aristotle's rhetorical framework. This approach is descriptive qualitative in nature. As a consequence of the findings, it was determined that Fuadh Naim is able to effectively use the components of ethos, pathos, and logos in his da'wah to establish credibility, manipulate emotions, and communicate logical reasoning. The findings are not only a source of knowledge and entertainment for Hallyu lovers, but also an effective platform for da'wah transmission by utilizing strong rhetorical principles and the relevance of the material provided